1973
DOI: 10.1139/v73-619
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Properties of Cyclopentanol + p-Dioxane Mixtures at 25 °C

Abstract: Excess enthalpies, excess volumes, and total vapor pressures were measured for cyclopentanol + pdioxane mixtures at 25 "C. The method of Barker was used to calculate vapor-liquid equilibria and excess Gibbs free energies from the vapor pressure results. apparaitre que les proprietes thermodynamiques d'exces des melanges cyclopentanol + p-dioxane resultent principalement de la rupture de la structure du solvant p-dioxane, dans ces melanges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…Densities of the pure liquids are listed in Table I. In general, agreement with literature data (26)(27)(28)(29)(30)(31)(32)(33)(34)(35) is satisfactory. Molar excess volumes as determined via eq 1 are presented in Tables II and III merits several months apart.…”
Section: Resultssupporting
confidence: 82%
“…Densities of the pure liquids are listed in Table I. In general, agreement with literature data (26)(27)(28)(29)(30)(31)(32)(33)(34)(35) is satisfactory. Molar excess volumes as determined via eq 1 are presented in Tables II and III merits several months apart.…”
Section: Resultssupporting
confidence: 82%
“…This is consistent with the dense packing of 1,3-dioxolane, 1,3-dioxane, and 1,4-dioxane (densities: 1058.66, 1028.69, and 1027.93 kg m −3 , respectively ,, ) and may explain the high Δ(Δ H vap ) value of 1,4-dioxane, which contrasts with its low μ̅. It has been suggested that the interactions between 1,4-dioxane molecules are mainly dispersive and of quadrupolar type . Thus, the significant order in cyclic diethers is modified upon mixing and large and positive H m E and V m E are obtained (Tables and ).…”
Section: Discussionsupporting
confidence: 77%
“…It has been suggested that the interactions between 1,4-dioxane molecules are mainly dispersive and of quadrupolar type. 77 Thus, the significant order in cyclic diethers is modified upon mixing and large and positive H m E and V m E are obtained (Tables 2 and 3). For mixtures with a given alkane, these excess functions change in the same sequence: tetrahydropyran < tetrahydrofuran < 1,4-dioxane < 1,3-dioxolane, in agreement with the relative variation of ∆(∆H vap ) (Table 6).…”
Section: Linear Polyether Systemsmentioning
confidence: 93%
“…This is consistent with the dense packing of 1,3-dioxolane, 1,3-dioxane and 1,4-dioxane (densities: 1058.66, 1028.69 and 1027.93 kg m −3 , respectively [53][54][55]), and may explain the high ( H vap ) value of 1,4-dioxane (5.29 kJ mol −1 [48]), which contrasts with its low . It has been suggested that the interactions between 1,4-dioxane molecules are mainly dispersive and of quadrupolar type [56]. Thus, the significant order in cyclic diethers is modified upon mixing and large and positive H E m are obtained.…”
Section: Oxaalkane + N-alkane Mixturesmentioning
confidence: 99%